A survey on network contraflow evacuation planningproblems - Bhandari, Phanindra Prasad; Khadka, Shree Ram (Journal of Science and Engineering, 2015)
Evacuation planning is becoming crucial due to an increasing number of natural and human-created disasters over last few decades. One of the efficient ways to model the evacuation situation is a network flow optimization model. This model captures most of the necessities of the evacuation planning. Moreover, dynamic network contraflow modeling is considered a potential remedy to decrease the congestion due to its direction reversal property and it addresses the challenges of evacuation route planning. However, there do not exist satisfactory analytical results to this model for general network. In this paper, it is tried to provide an annotated overview on dynamic network contraflow problems related to evacuation planning and to incorporate models and solution strategies to them developed in this field to date.